Poster Design Planning to Increase Community Motivation in using the Satu Sehat Application at Harapan Bunda Clinic Ngampel - Amanda Nadylla Kustina; Rumpiati Rumpiati (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
The Satu Sehat application was developed as an integrated electronic medical record platform. However, low public awareness and the absence of visual promotional media at Klinik Harapan Bunda Ngampel have resulted in minimal application usage. Therefore, a poster design is needed to increase public motivation to use the application. The study was conducted at Klinik Harapan Bunda Ngampel with participants including clinic staff, patients/family members, and a design expert. The method used was Research and Development (R&D) with a 3D model: Define (needs identification), Design (poster design), and Development (product testing and revision). The research took place from April to May 2025. The results showed that the designed poster contained essential information about Satu Sehat and was considered effective as a promotional medium. Validation by clinic staff and the design expert yielded scores of 84,28% and 90%, respectively, categorized as “good.” The poster was found to be attractive, easy to understand, and capable of increasing public motivation. The design of the poster to increase public motivation in using the Satu Sehat application at Klinik Harapan Bunda Ngampel proved effective in conveying information visually and can serve as a communication strategy to support digital transformation in healthcare services at the clinic.